Optimizing flavonoid-rich Quranic Mixed Food (QMF) formulation with simplex-centroid mixture design - N. M., Salbi; N., Muhammad; N., Abdullah (Rynnye Lyan Resources, 2021)
Quranic food, which defines as the food mentioned in the Holy Quran has gain attention as a functional food to prevent disease in the current era. The food had high potential as an excellent ingredient for the development of nutraceutical products. Flavonoid is one of the phytochemicals in Quranic food that contribute to their therapeutic properties. Unfortunately, there is less study on the health properties of Quranic food mixture that lead to misunderstanding of the mixture of Quranic food. A paramount concern regarding the addition of multiple bioactive ingredients into a product is the possibility of interaction among elements may result in degradation of the ingredient, and the functionality could be reduced or improved. Therefore, this study was aimed to optimize the flavonoid content of Quranic Mixed Food (QMF) containing dates, raisins, pomegranates, figs, and honey. Consequently, the special cubic model of simplex centroid design was employed as it was the most reliable and can be utilized in the optimization process as the p-value was significant, and the lack of fits was not substantial. The simplex centroid method had successfully optimized the QMF formulation. To conclude, the optimized formulation of flavonoid-rich QMF containing 42.88% raisins, 42.88% pomegranates, 13.97% honey, 0.17% dates, and 0.11% figs.